Auricular transcutaneous vagus nerve stimulation modulates the heart-evoked potential - Tasha Poppa; Lars Benschop; Paula Horczak; Marie-Anne Vanderhasselt; Evelien Carrette; Antoine Bechara; Chris Baeken; Kristl Vonck (Brain Stimulation, 2022)
Background: There is active interest in biomarker discovery for transcutaneous auricular vagus nerve stimulation (taVNS). However, greater understanding of the neurobiological mechanisms is needed to identify candidate markers. Accumulating evidence suggests that taVNS influences activity in solitary and parabrachial nuclei, the primary brainstem relays for the transmission of visceral sensory afferents to the insula. The insula mediates interoception, which concerns the representation and regulation of homeostatic bodily states. Consequently, interoceptive pathways may be relevant to taVNS mechanisms of action. Hypotheses: We hypothesized that taVNS would modulate an EEG-derived marker of interoceptive processing known as the heart-evoked potential (HEP). We also hypothesized that taVNS-induced HEP effects would be localizable to the insula. Methods: Using a within-subject, sham-controlled design, we recorded EEG and ECG concurrent to taVNS in 43 healthy adults. Using ECG and EEG data, we extracted HEPs. Estimation of the cortical sources of the taVNS-dependent HEP responses observed at the scalp were computed using the Boundary Element Method and weighted Minimum Norm Estimation. Statistics were calculated using cluster-based permutation methods. Results: taVNS altered HEP amplitudes at frontocentral and centroparietal electrode sites at various latencies. The taVNS-dependent HEP effect was localized to the insula, operculum, somatosensory cortex, and orbital and ventromedial prefrontal regions. Conclusion: The results support the hypothesis that taVNS can access the insula as well as functionally and anatomically connected brain regions. HEPs may serve as an objective, non-invasive outcome parameter for the cortical effects of taVNS.